PEMBERDAYAAN MASYARAKAT LUMAJANG MENGGUNAKAN TEKNOLOGI IOT PADA SEKTOR PARIWISATA - Shodiq, Muhammad; Prianto, Kusnul; Rifa'i, Muh. Khoirul; Wibowo, Achmad Teguh (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2025)
Lumajang district has very promising hydrographic potential for industry, drinking water, irrigation, and tourism. This research focuses on the use of internet of things (iot) technology as a new tool to improve the economy of lumajang communities, particularly in the tourism sector. Using a community based participatory research (cbpr) approach, this research involves the active participation of the community in the process. The results show that empowering the lumajang community with iot technology facilitates regular and structured monitoring of local revenue, particularly in the tourism sector. This has a positive impact on revenue management and the welfare of the people of lumajang district. With its hydrographic potential optimally utilized, the area can stimulate economic growth and the tourism sector, opening up new opportunities for local residents and regional stakeholders.